2000
DOI: 10.1055/s-2000-3837
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Electromyostimulation Training and Basketball Practice on Muscle Strength and Jumping Ability

Abstract: The aim of this study was to investigate the influence of a 4-week electromyostimulation training program on the strength of the knee extensors and the vertical jump performance of 10 basketball players. Electromyostimulation sessions were carried out 3 times weekly; each session consisted of 48 contractions. Testing was carried out before and after the electromyostimulation training program (week 4) and once more after 4 weeks of normal basketball training (week 8). At week 4, isokinetic strength increased si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
146
3
12

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(178 citation statements)
references
References 45 publications
16
146
3
12
Order By: Relevance
“…The moderate muscle hypertrophy and strength gains of the present study, however, were not sufficient to improve jumping performance. Studies that have demonstrated strength training induced improvements in jumping performance have reported much larger gains in muscle size and strength (Maffiuletti et al, 2000;Bruhn et al, 2004). It may be that longer KAATSU-training may cause larger muscle hypertrophy which might then be able to improve jumping performance.…”
Section: Discussionmentioning
confidence: 99%
“…The moderate muscle hypertrophy and strength gains of the present study, however, were not sufficient to improve jumping performance. Studies that have demonstrated strength training induced improvements in jumping performance have reported much larger gains in muscle size and strength (Maffiuletti et al, 2000;Bruhn et al, 2004). It may be that longer KAATSU-training may cause larger muscle hypertrophy which might then be able to improve jumping performance.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 During NMES application, the capacity to maintain performance is compromised compared to voluntary exercise, Experimental laboratory study.The primary purpose was to investigate the independent effects of current amplitude, pulse duration, and current frequency on muscle fatigue during neuromuscular electrical stimulation (NMES). A second purpose was to determine if the ratio of the evoked torque to the activated area could explain muscle fatigue.…”
mentioning
confidence: 99%
“…J Orthop Sports Phys Ther 2013; 43(12) 56 Although there is still a lack of strong evidence on the advantages of NMES compared to voluntary exercise, 6,21 training programs for athletes that include NMES have been investigated. 2,11,19,31,39 In soccer players, a 5-week training program using NMES produced increases in knee extension torque and ball speed with kicking, showing an improvement in the specific tasks of soccer. 7 However, more investigations are needed to examine the optimal stimulation parameters appropriate for NMES strengthening protocols in athletes.…”
Section: T T Conclusionmentioning
confidence: 99%
“…50 NMES has also been investigated for its potential role in helping to improve muscle performance in both healthy individuals and athletes. 21,31,39 In 1977, at a conference in Canada, the Russian scientist Yakov Kots reported on the use of a medium-frequency alternating current of 2500 Hz in Olympic athletes from the former Soviet Union and claimed that NMES could produce force gains of up to 40% in elite athletes compared to the use of exercises alone. These impressive strength gains were purportedly achieved by using NMES to elicit muscle contractions that were 10% to 30% greater than those achieved with a T T STUDY DESIGN: Repeated-measures, withinsubject crossover trial.…”
mentioning
confidence: 99%